The Effect of Dividend Policy and Company Size on Company Value with Tax Compliance Moderation Variables in The Coal Mining Sector - Jemmi Sutiono; H. Waluyo (Journal Research of Social Science, Economics, and Management, 2025)
This study examines the effect of dividend policy and company size on company value, with tax compliance as a moderating variable, focusing on the coal mining sector listed on the Indonesia Stock Exchange (IDX). The research problem stems from inconsistent findings in prior literature regarding the impact of dividend policy and company size on firm value, particularly in the volatile coal mining industry. The objectives are to: (1) analyze the influence of dividend policy on company value, (2) assess the effect of company size on firm value, and (3) evaluate the moderating role of tax compliance in these relationships. Using a quantitative approach, the study employs Moderated Regression Analysis (MRA) on secondary data from 103 energy sector companies (2020–2023). Results indicate that dividend policy negatively impacts firm value, contradicting the bird-in-hand theory, while company size has a significant positive effect. Tax compliance weakens the relationship between dividend policy and firm value, suggesting that higher tax obligations reduce funds available for dividends, thereby diminishing investor appeal. The findings contribute to corporate finance literature by highlighting the nuanced role of tax compliance in shaping firm value in resource-intensive industries. Practical implications include insights for managers on balancing dividend strategies with tax obligations and for policymakers in designing sector-specific fiscal regulations.